PENGARUH TEKNIK RELAKSASI NAFAS DALAM TRHADAP RESPON NYERI PADA IBU INPARTU KALA I FASE AKTIF DI PUSKESMAS BAHU KOTA MANADO - Novita, Kalalo Ribka; Rompas, Sefti; Bataha, Yolanda B. (JURNAL KEPERAWATAN, 2017)
Abstract : A pregnant mother’s pain scale at the first stage of the active phase of the average are in moderate to severe pain. Labor pain can be controlled by two methods, pharmacological and non pharmacological technique. In the pharmacological methods there are various methods, one of them is with deep breathing relaxation techniques. The purpose of this study is to see if deep breathing relaxation techniques on pain influences the pregnant mother’s active phase of the first stage at Puskesmas (Community Health Center) Bahu, City of Manado. This research design used is pre experiment with one group pretest-post design. The sampling technique used is an accidental sampling with a total 26 samples. The result of statistical tests T-test with a credible level of 95% (α=0,05) and obtained 0,000 p value <0,05. The conclusion is deep breathing relaxation techniques on pain does have an influence on the pregnant mother’s active phase of the first stage in Puskesmas (Community Health Center) Bahu, City of Manado. The suggestion of this study are expected to provide a reference for the development of independent intervention of nurse in non-pharmacological pain management. Keyword : Pregnant Mother’s First Active Phase, Pain, Deep Breathing Relaxation Techniques Abstrak : Skala nyeri pada ibu inpartu kala I fase aktif rata-rata berada pada skala nyeri sedang hingga berat terkontrol. Nyeri persalinan dapat dikendalikan dengan dua metode yaitu farmakologis dan non farmakologis. Pada metode non farmakologis terdapat berbagai metode, salah satunya dengan teknik relaksasi nafas dalam. Tujuan Penelitian mengetahui pengaruh teknik relaksasi nafas dalam terhadap respon nyeri pada ibu inpartu kala I fase aktif di Puskesmas Bahu Kota Manado. Desain Penelitian ini menggunakan pra eksperimen dengan pendekatan one group pretest-post design.. Teknik pengambilan Sampel menggunakan accidental sampling dengan jumlah sampel sebanyak 26 orang. Hasil Uji Statistik Wilcoxon signed rank test dengan tingkat kepercayaan 95% (α=0,05) dan diperoleh p value 0,000 < 0,05. Kesimpulan yaitu adanya Pengaruh Teknik Relaksasi Nafas Dalam Terhadap Respon Nyeri Pada Ibu Inpartu Kala I Fase Aktif di Puskesmas Bahu Kota Manado. Saran penelitian ini diharapkan dapat memberikan referensi bagi perkembangan intervensi mandiri perawat dalam manajemen nyeri non farmakologi. Kata kunci : Ibu Inpartu Kala I Fase aktif, Nyeri, Teknik Relaksasi Nafas Dalam